Shaping the Other in the Standardization of English: The Case of the ‘Northern’ Dialect - Ruano-García, Javier (International Journal of English Studies, 2020)
This paper explores the other side of standardization by looking at one of the early modern regional varieties of English that remained outside the “consensus dialect” (Wright, 2000: 6). Drawing on Agha’s (2003) framework of enregisterment, I examine a selection of literary representations of the ‘northern’ dialect that are now included in The Salamanca Corpus (García-Bermejo Giner et al., 2011–), as well as contemporary lexicographical evidence on northern words. My aim is to provide a window into contemporary ideas that saw and constructed the North as the ‘other’, whilst showing, as a result, that such views were immediately relevant to how the dialect and their speakers were imagined and represented alongside the emerging standard. To do so, I undertake a twofold quantitative and qualitative analysis of the evidence to identify the repertoire of forms that were associated with the dialect and the values attributed to such forms.